2022
DOI: 10.3389/fsurg.2022.829811
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Block of the Internal Branch of the Superior Laryngeal Nerve Reduces Postoperative Sore Throat Caused by Suspension Laryngoscopic Surgery: A Prospective Randomized Trial

Abstract: ObjectiveSuspension laryngoscopy is commonly used in operative laryngology. Although it is efficient and minimally invasive in most cases, it can lead to postoperative sore throat (POST) and cough. Because of intensive stimulation by the rigid metal suspension laryngoscope, procedures must be implemented under general anesthesia. Together, these factors increase the possibility of postoperative complications. Blocking the internal branch of the superior laryngeal nerve (SLN) is useful in inhibiting the endotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
15
2
Order By: Relevance
“…It is necessary to increase the sample size to determine whether the blockage of the medial branch of the superior laryngeal nerve can reduce the extubation reaction. Yin Bao et al found that block of the medial branch of superior laryngeal nerve can reduce the cardiovascular response during extubation, which is different from our findings [ 38 ]. The local anesthetic they used in their study was ropivacaine, which works longer than lidocaine.…”
Section: Discussioncontrasting
confidence: 99%
“…It is necessary to increase the sample size to determine whether the blockage of the medial branch of the superior laryngeal nerve can reduce the extubation reaction. Yin Bao et al found that block of the medial branch of superior laryngeal nerve can reduce the cardiovascular response during extubation, which is different from our findings [ 38 ]. The local anesthetic they used in their study was ropivacaine, which works longer than lidocaine.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicated that the blocking effect of US-guided iSLNB can last for 2 to 6 hours or longer, which is the same as the previous study. 31 It seems that this can be explained by the pharmacological characteristics of ropivacaine as an LA. Ropivacaine is a medium-long acting LA with an effective time of 4 to 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…is method of local nerve block is now widely used for fiberoptic bronchoscopy, laryngoscopy, and conscious intubation of difficult airway to reduce the hemodynamic change caused by airway stimulation and provide better practical conditions for operation [9][10][11][12]. Studies have shown that bilateral iSLN blocks can reduce cardiovascular response caused by the sympathetic stimulation during surgery [13] and reduce the incidence and severity of postoperative cough, sore throat, and hoarseness of voice [14,15]. erefore, it could be an ideal adjuvant to general anesthesia for SLVCP.…”
Section: Introductionmentioning
confidence: 99%